Optimalisasi Potensi Wisata Kota Melalui Integrasi Analisis Spasial dan SWOT: Studi Kasus Kecamatan Gambir, Jakarta Pusat - Aisahrul Hutami; Muhammad Imron Rosadi; CItra Lestari; Virsha Shofiyani; Deyan Arum Sitaresmi; Ahman Sya (Jurnal Sains Geografi, 2026)
Urban tourism played a strategic role in supporting economic and social development, particularly in central city areas with high historical and cultural value. Gambir District, Central Jakarta, contained several iconic tourist destinations; however, its tourism development still faced challenges related to spatial integration, supporting facilities, and intense urban activities. This study aimed to analyze the spatial distribution pattern of tourist destinations and to formulate integrated urban tourism development strategies. The research applied an integrated approach combining spatial analysis using Nearest Neighbor Analysis (NNA) and SWOT analysis based on secondary data. Tourist destination data were mapped using Geographic Information System tools to identify spatial distribution characteristics and were subsequently linked with internal and external factors influencing tourism development. The results showed that tourist destinations in Gambir District exhibited a significantly dispersed spatial pattern, reflecting the multifunctional characteristics of a central urban area. The integration of spatial analysis and SWOT analysis produced development strategies emphasizing improved connectivity between destinations, strengthening heritage-based area branding, and optimizing the use of digital tourism information systems. This study concluded that a dispersed spatial distribution of tourist destinations did not necessarily hinder tourism development, provided that it was managed through integrated spatial planning and sustainable urban tourism strategies.